Seasonal variation of streptococcal vulvo-vaginitis in an urban community - Morris, C. A. (1971)
A study was made of patients investigated by general practitioners. Over a three-year period Streptococcus pyogenes (group A) was isolated most commonly from vaginal and vulval swabs collected in the winter. The serotypes of strains indicate that some had probably been derived from the skin and others from the respiratory tract. The two sources are thought to have masked a consistent, but not obvious, seasonal variation in streptococcal vulvo-vaginitis acquired usually from streptococcal infections of the respiratory tract in winter and from those of the skin in summer.